MicroRNA-409-3p regulates macrophage migration in polymyositis through targeting CXCR4 - Qin Ye; Zhaoying Chen (Taylor & Francis Group, 2021)
Background Macrophage migration and infiltration contribute to the pathogenesis of polymyositis (PM). This study aims to investigate the effect and underlying mechanism of miR-409-3p on macrophage migration in PM. Methods The GSE143845 database was used to predict the altered expression of microRNAs (miRNAs) in PM. The quantitative real-time PCR (qRT-PCR), western blot and Transwell assay were performed to detect migration of macrophages and expressions of related molecules. A luciferase activity assay was conducted to confirm the binding of miR-409-3p and CXCR4 3'-UTR. Next, a mouse model of experimental autoimmune myositis (EAM) was established. Haematoxylin and eosin (HE) staining, immunohistochemistry (IHC), and enzyme-linked immunosorbent assay (ELISA) were used to measure associated factors. Results MiR-409-3p was downregulated in PM of GSE143845 database and patients. Differently, the serum creatine kinase (s-CK), TNF-α, and IL-6 in patients with PM were increased. Furthermore, miR-409-3p mimic transfection reduced the migration of macrophages and CXCR4 levels, while miR-409-3p inhibitor exerted the opposite effects. CXCR4 was a target of miR-409-3p, and the effect of CXCR4 on promoting macrophage migration was reversed by miR-409-3p mimic. In vivo, miR-409-3p agomir injection reduced inflammatory cells, macrophages, and TNFα and IL-6 levels in muscles and serum of EAM mouse models. Conclusions In conclusion, miR-409-3p reduces the migration of macrophages through negatively regulating CXCR4 expression in PM.